Validation and relaibilty study of exercise dependence scale–21 in Turkish - Yeltepe, Hülya; İkizler, H. Can (Journal of Dependence, 2007)
Objective: Exercise Dependence Scale-21 is a 21 item self-reported scale developed by Hausenblas ve Downs (2002) to examine exercise dependece. The purpose of this study was to describe the concept of exercise dependence and to provide reliability and validation study for the Turkish version of the Exercise Dependence Scale–21 (EDS-21) that examine exercise dependence among the participants who exercise for a long time in high intensity and frequency. Method: This study was conducted with exercisers for two years or more in Pamukspor, Daruşşafaka, Enka and ITU Sports Centers in Istanbul and non-exercisers for two years or more. One hundred twenty four participants who identified their frequency of exercise per week as either non-exerciser (n=38), three or four days per week (n=41) and five days and more per week (n=45) for two years or more were included in the study. This study has twofold. In the first part, the EDS-21 was administred to the participants to provide two weeks test-retest reliability and validation. In the second part of the study, exercise dependence was examined among the participant group. The relationship between exercise dependence and years of participation to exercise and frequency of exercise per week was also examined. Results: Reliability analysis (Cronbach Alpha) for both administiration with result of alpha for the first administiration (Cronbach) a=0.96 and (Cronbach) a=0.97 for the second administiration. Also Pearson Correlation between test and retest for all items has been found to be highly significant (P<0.001). N=14 participants are classified as exercise dependent in the participants group. It was found that exercise dependence is more prevalent among the participansts who exercise five or more days/week (n=13) for five years or more (n=10). This results demonstrated positive relationship with exercise dependence and years of participation to exercise and frequency of exercise per week. Conclusion: Results of this study suggests that Turkish version of EDS –21could be used as reliable and valid tool to examine exercise dependence among the individuals who exercise for a long time in high intensity and frequency.